Pengaruh Digitalisasi Terhadap Kinerja Karyawan Koperasi: Survey Pada Koperasi Anggota Puskhat Mitra PT. USSI Pinbuk Prima Software - Supriyadi, Deddy; Hendrawan Purnomo, Dede (Coopetition : Jurnal Ilmiah Manajemen, 2024)
One of the efforts being made in the current era to improve the performance of companies and employees in their operations and services, including cooperatives, is by implementing digital technology (digitization). Among the cooperatives that have digitalized are Credit Unions (primary CU) members of the Pusat Koperasi Kredit Khatulistiwa (Puskhat). The aim of this research is to determine the implementation of digitalization in Puskhat member cooperatives, the performance of cooperative employees after digitalization and the extent of the influence of cooperative digitalization on employee performance. The research methods are survey and quantitative descriptive methods using correlation regression analysis The results of the research show that the overall implementation of digitalization of Puskhat member cooperatives is going very well, the performance of cooperative employees has increased very well and there is a positive linear relationship between digitalization of cooperatives and the performance of their employees. The hypothesis can be accepted, it is proven that the digitalization of cooperatives has a significant positive effect on employee performance. In order for digitalization in Puskhat member cooperatives to be more effective, it is necessary to carry out continuous digitalization training, changes in organizational culture, documented software maintenance and software upgrades in accordance with developments and needs, as well as objective employee performance assessments related to competency in using digitalization.